NLP Story Maker - Aikawa, Takako; Pahud, Michel; Schwartz, Lee (L&TC’05, 2nd Language & Technology Conference: Human Language Technologies as a Challenge for Computer Science and Linguistics, 2005)
This paper explores a novel approach to linking Graphics and Natural Language Processing (NLP). Our tool, Story Maker, lets users illustrate their stories on the fly, as they enter them on the computer in natural language. Our goals in creating Story Maker are twofold: to explore the use of NLP in the dynamic generation of animated scenes, and to explore ways to exploit users' input in order to obviate the necessity of having a large database of graphics. With our NLP technology, users can input unrestricted natural language. Story Maker provides users with direct visual output in response to their natural language input. The tool can potentially impact both the way we interact with computers and the way we compose text.